2019
DOI: 10.5860/crl.80.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Academic Librarians Serving as Interim Library Leaders

Abstract: Using a mixed-methods approach, the researchers explored the experiences of 108 academic librarians who served as interim library leaders at U.S. institutions of higher education between 2012 and 2017. Statistical analysis showed no associations between gender, type of institution, or degree-granting level with the duration of interim service or whether a respondent applied for or was hired as the permanent leader. The authors provide recommendations for future interim library leaders and the university execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Although the challenges of serving as interim managers were considerable, so were the rewards. As others have noted, we found that the financial rewards of our interim roles were insignificant compared to the most meaningful rewards, which were intrinsic (Weingart 2003;Farrell 2016;Irwin and deVries 2019). One of the most noteworthy rewards we found in our service as interim managers was that working with public services raised our own morale.…”
Section: Challenges and Rewardsmentioning
confidence: 47%
See 2 more Smart Citations
“…Although the challenges of serving as interim managers were considerable, so were the rewards. As others have noted, we found that the financial rewards of our interim roles were insignificant compared to the most meaningful rewards, which were intrinsic (Weingart 2003;Farrell 2016;Irwin and deVries 2019). One of the most noteworthy rewards we found in our service as interim managers was that working with public services raised our own morale.…”
Section: Challenges and Rewardsmentioning
confidence: 47%
“…Interim leaders and managers can have an enormous impact on an organization and, when successful, are instrumental in supporting the health of both the organization and its personnel. A number of variables influence the level of success an interim leader experiences (Irwin and deVries 2019). With regard to any positive impact we had while serving as interim managers, we credit our servant leader approach, the expertise and dedication of the individuals we oversaw, and the support of colleagues at every level of the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation